2006
DOI: 10.1007/11783565_21
|View full text |Cite
|
Sign up to set email alerts
|

On-Demand Quality-Oriented Assistance in Component-Based Software Evolution

Abstract: Abstract. During an architectural evolution of a component-based software, certain quality attributes may be weakened. This is due to the lack of an explicit definition of the links between these non-functional characteristics and the architectural decisions implementing them. In this paper, we present a solution that aims at assisting the software maintainer during an evolution activity on his demand. It requires the definition of a documentation during development, organized in the form of bindings between f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 15 publications
0
26
0
Order By: Relevance
“…It has been demonstrated that architecture constraints bring a valuable help for preserving architecture styles, patterns or general design principles in a given application after having evolved its architecture description [24]. These architecture constraints are checked at design time.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that architecture constraints bring a valuable help for preserving architecture styles, patterns or general design principles in a given application after having evolved its architecture description [24]. These architecture constraints are checked at design time.…”
Section: Resultsmentioning
confidence: 99%
“…This ensures easy and safe evolution (maintenance) activities on the software. Indeed, among the maintenance activities, understanding the software architecture before its evolution, and iterations between regression testing and applying concrete changes on the software, are by far the most expensive (52). By making the most important architectural choices explicit and formal, on the one hand, we facilitated the architecture comprehension (through knowledge documentation) and on the other, we automated some checking that allows an assistance to the evolution activity.…”
Section: Discussionmentioning
confidence: 99%
“…This assistance notifies developers on-the-fly, whenever an architectural change affects the documented architectural choices. This contributes in reducing the costs related to the software evolution activity by anticipating some regression tests, as detailed in (52).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Architecture constraints are used during the evolution of a software architecture for guaranteeing that changes do not have bad side effects on the applied architecture patterns or styles, and thus on the quality [28].…”
Section: Introduction: Context and Problem Statementmentioning
confidence: 99%